Perancangan Aplikasi Jadwal Liputan Berbasis Web Di Bidang Berita TVRI Dengan Metode Prototype - Andika Panji Hermawan; Leni Susanti; Emi Sita Eriana; Ghema Nusa Persada (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
The absence of an application to assist in the scheduling of the Communication and Informatics department's duties at TVRI has resulted in ineffective schedule distribution, causing a TVRI staff member to receive two coverage schedules simultaneously, while others may not receive any schedule at all. The purpose of this final report is to create an Application for Coverage, Announcers, and Editorial Schedules at TVRI using the PHP programming language with the Laravel framework and MYSQL database, and designing its interface using Bootstrap. The issue faced by TVRI's Communication and Informatics Department (Diskominfo) is the operational data processing of broadcasting schedules using Microsoft Excel, which poses several challenges including insufficient data security, unorganized data storage making it difficult to search, and the risk of losing previously saved data, thereby slowing down TVRI's reporting process. This application comprises three User levels: admin, User, and TVRI head. The research adopts the Prototype development method to create the Coverage, Announcers, and Editorial Schedule Application at TVRI. Through the Prototype, the development team can quickly visualize the application's design and functionality, gather early User feedback, and address potential issues or design improvements before full implementation. The research outcome, in the form of the application, provides a concrete solution to the challenges of scheduling effectiveness at TVRI, enhancing efficiency, addressing data security concerns, ensuring organized data storage, and improving workflow speed.